A juristic study on investment of awqaf: from classical to contemporary modes - Osmani, Noor Mohammad; Rahman, Md. Habibur (INSI Publications, 2015)
Awqaf (endowments) had played a significant role in the progress and development of human civilization. It is a need of time to revitalize the roles of awqaf for the advancement of human society and civilization. Hence, this paper intends to make a juristic study on utilizing awqaf funds through investment and financing based on the classical to the contemporary modes. The paper will be qualitative in nature, in which analytical and descriptive methods will be followed. The analysis primarily relies on classical and contemporary juristic views and discussion. The paper claims that the investment of awqaf properties could be accomplished in two forms, investment of the original awqaf assets and investment of its proceeds. The investment modes to be analyzed in the paper are, for example, hikr (long lease with large advance lump sum), lease with dual payment, kadik (tenant's improvements to rental property), mursad (construction for rent swap with a waqf), sharecropping, partnership, diminishing partnership, manufacturing arrangement, lease ended with ownership as well as investment in purchasing permissible financial papers and securities. The paper also explains the issue of substitution and modification of awqaf properties as it is of paramount importance in handling the awqaf properties for the welfare of society.